2020
DOI: 10.1007/s00431-020-03761-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in minute alveolar ventilation causes hypercapnia in ventilated neonates with respiratory distress

Abstract: Hypercapnia occurs in ventilated infants even if tidal volume (V T) and minute ventilation (V E) are maintained. We hypothesised that increased physiological dead space (V d,phys) caused decreased minute alveolar ventilation (V A ; alveolar ventilation (V A) × respiratory rate) in well-ventilated infants with hypercapnia. We investigated the relationship between dead space and partial pressure of carbon dioxide (PaCO 2) and assessed V A. Intubated infants (n = 33; mean birth weight, 2257 ± 641 g; mean gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…10 A previous study has shown that a reduction in alveolar ventilation resulted in hypercapnia in ventilated infants with respiratory distress syndrome (RDS). 11 The aim of this study was to determine if the physiological dead space in prematurely born infants with RDS or evolving/established bronchopulmonary dysplasia (BPD) was greater than in term controls with no respiratory disease. We further aimed to determine whether the size of the dead space influenced the alveolar ventilation in mechanically ventilated infants.…”
Section: Introductionmentioning
confidence: 99%
“…10 A previous study has shown that a reduction in alveolar ventilation resulted in hypercapnia in ventilated infants with respiratory distress syndrome (RDS). 11 The aim of this study was to determine if the physiological dead space in prematurely born infants with RDS or evolving/established bronchopulmonary dysplasia (BPD) was greater than in term controls with no respiratory disease. We further aimed to determine whether the size of the dead space influenced the alveolar ventilation in mechanically ventilated infants.…”
Section: Introductionmentioning
confidence: 99%
“…We had previously reported the use of volumetric capnography based on ventilator graphics and capnograms in ventilated neonates in NICUs by using a commonly used lightweight mainstream capnometer. 8,9 We hypothesized that ventilated infants with hypoxemic respiratory failure (HRF) show a large difference between V d, Enghoff and V d, Bohr . Thus, the objective of this study was to measure both V d, Enghoff and V d, Bohr, and to detect low V/Q mismatch and right-to-left shunting in intubated neonates by using volumetric capnography based on ventilator graphics and capnograms.…”
Section: Introductionmentioning
confidence: 99%